(untitled) (Plant Tissue Culture and Biotechnology, 2011)
Triadimefon, a triazole compound increased survival per cent of micropropagated Gladiolus (Gladiolus grandiflorus L.) plantlets. Applica-tion of triadimefon caused a retarding effect on height of the plant (14.86 cm) compared to the untreated plants one month after planting to ex vitro conditions. Triazole application increased root number of the plants. Plants treated with triazole showed delayed leaf production interval of 10.45 and 14.48 days for first and second leaves, respectively. Triazole treated plants exhibited a lower stomatal conductance which indicated the reduced water loss from the leaves. Leaf area index was high for untreated plants(1.08) compared to treated plants. Key words: Gladiolus, Triazole, Micropropagation,Triadimefon, Acclimatization D.O.I. 10.3329/ptcb.v20i2.6896 Plant Tissue Cult. & Biotech. 20(2): 171-178, 2010 (December)